Study of Interactions of Microscopic Fungi Isolated from Burrow Microbiotopes of Great Gerbil and Little Souslik with Plague Agent and its Vectors - N. V. Lopatina; B. N. Mishankin (Эпидемиология и вакцинопрофилактика)
At present there is strong evidence of the long-term persistence of Yersinia pestis in soil during interepizootic period in nonculturable and L-forms of bacteria. This information helps to reveal the mechanisms of emergence, establishment and extinction of plague foci. Deciphering causes of transformation of plague microbe in rodent burrows is possible only under condition of detailed study of biocenotic relations of plague causative agent with each of the multiple biocenosis components, including microorganisms -permanent inhabitants of the burrow microbiotopes in natural plague foci. Purpose of the study: Study of interactions of microscopic fungi-micromycetes iso-lated from burrow microbiotopes of great gerbil and little souslik in the Ural-Emba interfluve and in Nogai steppe with plague agent and its vectors. Materials and methods: The effect of 74 micromycete species, isolated in natural plague foci, on Yersinia pestis virulent strains was studied in vitro and in vivo (in organisms of X. skrjabini fleas). In the experiments in vitro fungi metabolites were applied on the lawns of Y. pestis test-cultures with subsequent recording of the size of lysed zones. Fleas were challenged in tubes with filtering-paper strips impregnated by fungal cultural liquid and then LT100 value was calculated. In the experiments in vivo fungus conidia were applied on the surface of insect cuticle; flea challenging with plague was carried out on agonizing white mice infected by plague microbe. Insect challenge with plague and fungal conidia was alternated in different succession. Results and discussion: Of 74 micromycete strains 78.4% produced antagonistic effect in relation to 1-5 Y. pestis strains. Ashergillus versicolor, A. clavatus, A. sulfereus, Mucor racematus, Penicillium baarnensens, P. sp. relative to P. charlesii, P. sp. relative to P. martensii, P. insectus, P. chrysogenum fungi induced growth suppression of all five test strains of Y. pestis. High antibiotic activity of fungi metabolites was accompanied by insecticidal activity against Xenopsylla skrjabini fleas. Microscopic fungi P. funiculosum, P. cyclopium, P. chrisogenum, P. charlesii. P. canescens, A. versicolor induced 100% flea death on 4-6 day. As a result of insect pretreatment by conidia of P. funiculosum with subsequent challenging with plague microbe block formation in fleas decreased 14 times, and the number of Y. pestis cells after 12 days was 25-33 times less independent of succession, in which insects were challenged with microorganisms. Conclusion. It is supposed that micromycetes could play an important role in natural plague foci, adjusting epizootic activity of plague vectors and causative agent.